Miniature Modular Reconfigurable Underwater Robot Based on Synthetic Jet - Dehong Wang; Fanheng Zhang; Shijing Zhang; Daqing Liu; Jing Li; Weishan Chen; Jie Deng; Yingxiang Liu (Advanced Science)
Abstract Modular reconfigurable robots exhibit prominent advantages in the reconnaissance and exploration tasks within unstructured environments for their characteristics of high adaptability and high robustness. However, due to the limitations in locomotion mechanism and integration requirements, the modular design of miniature robots in the aquatic environment encounters significant challenges. Here, a modular strategy based on the synthetic jet principle is proposed, and a modular reconfigurable robot system is developed. Specialized bottom and side jet actuators are designed with vibration motors as excitation sources, and a motion module is developed incorporating the jet actuators to realize three‐dimensional agile motion. Its linear, rotational, and ascending motion speeds reach 70.7 mm s−1, 3.3 rad s−1, and 28.7 mm s−1, respectively. The module integrates the power supply, communication, and control system with a small size of 48 mm × 38 mm × 38 mm, which ensures a wireless controllable motion. Then, various configurations of the multi‐module robot system are established with corresponding motion schemes, and the experiments with replaceable intermediate modules are further conducted to verify the transportation and image‐capturing functions. This work demonstrates the effectiveness of synthetic jet propulsion for aquatic modular reconfigurable robot systems, and it exhibits profound potential in future underwater applications.